2023
DOI: 10.1111/cns.14367
|View full text |Cite
|
Sign up to set email alerts
|

The G protein‐coupled estrogen receptor of the trigeminal ganglion regulates acute and chronic itch in mice

Abstract: AimsItch is an unpleasant sensation that severely impacts the patient's quality of life. Recent studies revealed that the G protein‐coupled estrogen receptor (GPER) may play a crucial role in the regulation of pain and itch perception. However, the contribution of the GPER in primary sensory neurons to the regulation of itch perception remains elusive. This study aimed to investigate whether and how the GPER participates in the regulation of itch perception in the trigeminal ganglion (TG).Methods and ResultsIm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Overall, although itch has been scientifically recognized for 360 years, we have only begun to gradually understand its underlying mechanisms in the last 20 years. Itch and neuroimmunology research has identified potential mechanisms in terms of nerve transmission, 57 immune cells, 15 and inflammatory factors, 16 which provide the basis for biologically targeted agents to treat pruritic diseases. However, various research directions still deserve further exploration and focus.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, although itch has been scientifically recognized for 360 years, we have only begun to gradually understand its underlying mechanisms in the last 20 years. Itch and neuroimmunology research has identified potential mechanisms in terms of nerve transmission, 57 immune cells, 15 and inflammatory factors, 16 which provide the basis for biologically targeted agents to treat pruritic diseases. However, various research directions still deserve further exploration and focus.…”
Section: Discussionmentioning
confidence: 99%